Co-occurrence of nitrogen-converting organisms in full-scale treatment plants - BAKIRCI, KOZET (TAYLOR & FRANCIS INC, 2010)
This study provides insights into nitrogen-converting microorganisms in three full-scale wastewater treatment plants (WWTPs), which were investigated and monitored according to their nitrification performance and the presence of ammonia-oxidizing bacteria (AOB), nitrite-oxidizing bacteria (NOB), ammonia-oxidizing archaea (AOA), and Anammox bacteria based on different molecular tools: fluorescent in situ hybridization (FISH), slot-blot hybridization, and quantitative real-time PCR. In situ hybridization clearly showed the Nitrosomonas species as the prevailing AOB, and Nitrospira-related species as the dominant NOB. Real-time PCR results exposed the Istanbul Pasakoy, Bursa West, and Bursa East WWTPs as harboring diverse nitrogen-converting microbial communities that include AOB, NOB, AOA, and Anammox bacteria. Nitrospira species had the highest fraction of nitrogen-converting organisms, which was up to 39.3% in the WWTPs throughout the two-year monitoring period. This study is the first molecular analysis of the simultaneous occurrence of these microorganisms.
Keywords: Ammonia and nitrite oxidizing bacteria; ammonia oxidizing archaea; Anammox; ANAEROBIC AMMONIUM OXIDATION; WATER TREATMENT PLANTS; 16S RIBOSOMAL-RNA; GRADIENT GEL-ELECTROPHORESIS; NITRITE-OXIDIZING BACTERIA; REAL-TIME PCR; ACTIVATED-SLUDGE; MICROSCALE DISTRIBUTION; QUANTITATIVE-ANALYSES; NITRIFYING BACTERIA